Penelitian pembuatan sol karet dengan carbon black sebagai filler - Prayitno, Prayitno (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1986)
Carbon black is a reinforcing filler which can improve the physical properties of rubber products, such as : Rensile strength, abrassion resistance. This physical properties will be resched the highest values and after that the physical properties decrease. At 80% of carbon black utilization gives the best physical properties, it is 87,6567 kg/cm2 tensile strength, 148 elongation at break, hardness 85 shore A, density 1,24 g/cm3, abrasion resistance 1,232 mm3/kgm, flex cracking resistance is good (without any cracks), permanent set 100% is 3,80.